Manipulating fungal growth in engineered living materials through precise deposition of nutrients - Teoh, Jia Heng (2024)
One main challenge of emerging fungal-based engineered living materials (ELMs) lies in achieving localized multi-material properties in these structures. Although three-dimensional (3D) printing can efficiently vary local composition and properties, it has not yet been demonstrated in fungal-based ELMs. This work thus explores the concept of using nutrients to manipulate fungal foraging behavior in 3D structures fabricated using direct ink writing (DIW) for the next generation of fungal-based ELMs. Using two fungal strains (Pleurotus ostreatus and Ganoderma lucidum), this study shows that the ink formulation used is suitable for both DIW and mycelium growth. Varying the nutrient content allows for either the inhibition or promotion of exploration and bridging of mycelium in different sections, the control of mycelium density in three dimensions and the fabrication of patterned surfaces. There is potential in fabricating patterned fungal-based ELMs and lab-on-a-chip systems to investigate the effects of other substances and microorganisms on the foraging behavior of mycelium.